Manajemen Pendidikan dalam Perspektif Al-Qur’an dan Hadis - Muarifah, Muarifah; Sani, Mutiara; Anshory, Muhammad Isa (TSAQOFAH, 2025)
This study examines educational management from the perspective of the Qur’an and Hadith, emphasizing that fundamental managerial concepts have been embedded in Islamic teachings since the beginning of creation. In Islam, all aspects of life, including the management of education are comprehensively addressed in the Qur’an and Hadith. The concept of management is reflected in the creation of the universe, the organization of living beings, and the appointment of Prophet Adam (AS) as a khalifah, entrusted to lead the earth based on principles of orderly and systematic governance. The objective of this research is to explore the concept of educational management derived from the Qur’an and Hadith, identify their practical guidance within the context of education, and explain the urgency of their implementation in contemporary educational systems. This study adopts a library research method with a qualitative-reflective approach. The findings indicate that interpretations of managerial principles in the Qur’an and Hadith are highly relevant for shaping an effective educational environment rooted in spiritual values and aligned with Islamic teachings. By applying revelation-based educational management, holistic educational goals can be achieved more optimally.